Hashtag activism in the advancement of social change: an examination of the #metoo movement and its techno-social implications - Kittredge, Rayna Elizabeth (Kansas State University, 2022)
In 2017, actress Alyssa Milano tweeted “If all the women who have been sexually harassed or assaulted wrote ‘Me too’ as a status, we might give people a sense of the magnitude of the problem.” (Lindgren, 2019) The response to this tweet became the viral hashtag activist movement #metoo across social platforms. As an exemplar of digital activism, the #metoo movement offers scholars an opportunity to explore how social media alters the activism landscape, stitching feminism and technology together for the social advancement of gendered protesting. Simultaneously allowing the technical architectures of Twitter and affordances of the categorically enabled hashtag allowed for a worldwide debate on gender, violence, and power (Lindgren, 2019). The research synthesized in this report examines key literature on digital activism, rhetoric, and social media, using the case of the #metoo movement to clarify this activism’s expressions. The research presented in this report examines how digital rhetoric, intertextuality, and advances in techno-social connectivity have advanced communication in social networking. In particular, the report will examine key literature on online social movements, the communicative affordances of digital connectivity, and hashtag activism. The research presented analyzes several aspects of digital communication, with a particular focus on affordances that encourage hashtag activism. The report situates the #metoo movement as an exemplar of hashtag activism that supports the advancement of social change. First, this report will evaluate the role of hashtag categorization in social platforms using the viral #metoo movement as a vehicle for modern protesting without the constraints of space and time (Kurniawan et al., 2020). Then, it will evaluate scholarly literature on the rhetorical implications of digital texts (Eyman, 2015) and the intertextual possibilities of digital activism. Lastly, the report will evaluate key aspects of technofeminist theory, which Wajcman (2010) and others have argued as potentially emancipatory. The report offers a synthetic contribution to the continued study of gender discourse and highlights the power of visceral shared experiences within the digital sphere.
Keywords: Hashtag; Feminism; Activism; Twitter